Prognostic values of geriatric nutrition risk index on elderly patients after spinal tuberculosis surgery - Huang, Yong; Wu, Ruibang; Xia, Qinghong; Liu, Limin; Feng, Ganjun (Frontiers in Nutrition, 2023)
Background Spinal tuberculosis (STB) is a significant public health concern, especially in elderly patients, due to its chronic and debilitating nature. Nutritional status is a critical factor affecting the prognosis of STB patients. The geriatric nutritional risk index (GNRI) has been established as a reliable predictor of adverse outcomes in various diseases, but its correlation with surgical outcomes in elderly STB patients has not been studied. Objective The study aimed to assess the prognostic value of the GNRI in elderly patients with STB who underwent surgery. Methods We conducted a retrospective analysis of medical records of elderly patients (65 years or older) diagnosed with active STB who underwent surgical treatment. Data collection included patient demographics, comorbidities, clinical history, laboratory testing, and surgical factors. GNRI was calculated using serum albumin levels and body weight. Postoperative complications were observed and recorded. The patients were followed up for at least 1 year, and their clinical cure status was assessed based on predefined criteria. Results A total of 91 patients were included in the study. We found that a GNRI value of <98.63 g/dL was a cutoff value for predicting unfavorable clinical prognosis in elderly STB patients undergoing surgery. Patients with a low GNRI had higher Charlson Comorbidity Index scores, were more likely to receive red blood cell transfusions, and had a higher prevalence of overall complications, particularly pneumonia. The unfavorable clinical prognosis group had lower GNRI scores compared to the favorable prognosis group. Multivariate analysis showed that lower GNRI independently predicted unfavorable clinical outcomes in elderly STB patients. Conclusion The study concluded that the GNRI is a valuable biomarker for predicting prognosis in elderly STB patients undergoing surgical intervention. Patients with lower GNRI scores had worse outcomes and a higher incidence of complications.